Bilio-pancreatic endoscopy during COVID-19 pandemic - Vincenzo Bove; Tommaso Schepis; Ivo Boškoski; Rosario Landi; Beatrice Orlandini; Valerio Pontecorvi; Pietro Familiari; Andrea Tringali; Vincenzo Perri; Guido Costamagna (Therapeutic Advances in Gastroenterology, 2020)
On 31 December 2019, the WHO China Country Office was informed of cases of pneumonia of unknown etiology detected in Wuhan (Hubei Province of China). In January 2020, a new coronavirus named SARS-CoV2 was isolated and, since that time, SARS-CoV2 related disease (COVID-19) rapidly spread all over the world becoming pandemic in March 2020. The COVID-19 outbreak dramatically affected the public-health and the health-care facilities organization. Bilio-pancreatic endoscopy is considered a high-risk procedure for cross-contamination and, even though it is not directly involved in COVID-19 diagnosis and management, its reorganization is crucial to guarantee high standards of care minimizing the risk of SARS-CoV2 transmission among patients and health-care providers. Bilio-pancreatic endoscopic procedures often require a short physical distance between the endoscopist and the patient for a long period of time, a frequent exchange of devices, the involvement of a large number of personnel, the use of complex endoscopes difficult to reprocess. On this basis, endoscopic units should take precautions with adjusted management of bilio-pancreatic endoscopy. The aim of this article is to discuss the approach to bilio-pancreatic endoscopy in the COVID-19 era with focus on diagnostic algorithms, indications, management of the endoscopic room, proper use of Personal Protective Equipment and correct reprocessing of instrumentation.